The Two Sides of Mimesis: Mimetic Theory, Embodied Simulation, and Social Identification - Gallese, Vittorio (Mimesis and science, 2011)
René Girard (b. 1923), French literary critic and anthropologist, has provided us with an incredibly rich and thought-provoking theory of human culture: Mimetic Theory. What is most fascinating in Girard?s Mimetic Theory is its broad and bold scope. According to Girard, human culture sits on the shoulders of religion, which in turn stems from the ritualization of social violence through the mechanism of scapegoating. As Girard wrote in Violence and the Sacred , "My theory is the first to offer an explanation of the primordial role that religion plays in primitive societies, as well as of man?s ignorance of this role."